MEMBANGUN SISTEM INFORMASI GEOGRAFIS PERGURUAN TINGGI DAERAH ISTIMEWA YOGYAKARTA BERBASIS WEB - Suratmo, Dodo; ., Suraya; Widyastuti, Naniek (Jurnal Script, 2014)
ABSTRACTGeographic Information Systems (GIS) is an integrated way of working software / hardware for accessing geospatial data and services through mobile devices via wired or wireless network. With the development of GIS, can be used as a background in basic research Yogyakarta Province is known as the city of education in Indonesia. To accommodate the users, especially young people in terms of a simple navigation with regard to accessing the location of the existing universities in the province of Yogyakarta. Then the application of GIS Higher Education Location Yogyakarta Province is appropriate to meet those needs. Navigation is simple to locate universities located in the province of Yogyakarta. By utilizing Google Maps that can be used free of charge and also do not need to make a special server for managing data associated with a virtual map. Application is expected to simplify the user application to determine the location of universities with blue marker display is located in the maps. Facilities directions college is a facility that can provide information to the user about the information that must be taken by the user to be to the location of the college sought, and the information is displayed in the form of a map showing the roads, street names and mileage information. Prody search feature is a facility that can provide information on the accreditation department so that the user can determine the level of college accreditation is sought.Keywords: Geographic Information Systems, GIS Applications, Higher Education, Google maps, Special Region of Yogyakarta